Communities of violence persecution of minorities in the middle ages - Nirenberg, David (Princeton University Press, 2015)
Nirenberg shows that their use of violence expressed complex beliefs about topics as diverse as divine history, kingship, sex, money, and disease, and that their actions were frequently contested by competing groups within their own society.